Comparison of percutaneous intramedullary Kirschner wire and interfragmentary screw fixation of displaced extra-articular metacarpal fractures. - Biz, Carlo; Iacobellis, Claudio (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: the management of the displaced extra-articular metacarpal fractures is still a subject of debate in the literature. The purposes of this study were to report the outcomes of unstable extra-articular metacarpal fractures treated by using intramedullary Kirschner wires or inter-fragmentary screws and to determinate which techniques provide better clinical and radiographic results. Methods: we retrospectively reviewed a series of 49 consecutive patients operated for 53 closed, unstable metacarpal fractures. The fractures were divided into two groups, according to the fixation method used: the percutaneous intramedullary K-wire fixation group and the interfragmentary screw fixation group. The injuries were classified on the basis of fracture level and type. Assessment of patients was carried out according to the Mayo Wrist and Dash Scoring systems. Finally, radiographic and clinical outcomes of both groups were assessed and compared. Results: there were no significant differences between the two groups related to follow-up, hospitalization days, operating time, and Mayo Wrist and Dash Scores. Bone union was achieved within 6 weeks in all patients. Nine cases of malunion were found, with a mean angular deformity of 8.33° (range, 5°-15°), of which 8 were patients treated with K-wires (mean 8.125°) and 1 with screws (10°). Conclusion: our results indicate that both procedures are effective in the treatment of displaced extra-articular metacarpal fractures. However, we believe K-wires represent the gold standard of treatment for displaced fractures of the metacarpal neck. Instead, screws are more effective for spiroid shaft fractures, while displaced fractures of the base may be treated with either screws or wires.